PENDIDIKAN MULTIKULTURAL BERBASIS SENI BUDAYA DI SD TAMAN MUDA IBU PAWIYATAN YOGYAKARTA - Dwi Wijayanti; Poppy Indriyanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
This research aims to : (1) describe the education multicultural through the education based on culture and art at SD Taman Muda Ibu Pawiyatan Yogyakarta, (2) identify obstacle in applying the education multicultural through the education based on culture and art at SD Taman Muda Ibu Pawiyatan Yogyakarta, and (3) find solutions to overcome the obstacles in education multicultural through the education based on culture and art at SD Tama Muda Ibu Pawiyatan Yogyakarta. This was a qualitative research. In order to gain data, the researcher used interview, direct observation and documentation. The data analysis techniques used steps of Miles and Huberman’ model such as data collection, data reduction, data presentation and verification, while the data validation included internal validation, external validation, reliability and objectivity. The result of the research showed that (1) education multicultural based on culture and art at SD Taman Muda Ibu Pawiyatan Yogyakarta was not taught in a special  lesson but integrated into  lessons (intracurricular) such as Ketamansiswaan, Pkn, SBK, SeniTari, Batik, Bahasa Indonesia, Karawitan, Tembang and BahasaJawa. Discoveringthe multicultural values and culture and art through self-developed activity was done by creating a condusive school culture and extracurricular activities which include dolanan anak, senilukis, bahasa jawa, pencaksilat, pramuka, drumband and pianika. (2) The obstacles experienced were low teacher competence, difficulties in learning bahasa jawa, the minimum of learning media and facilities, the influence of students’ association outside school and technology, and special need students. The strategies to overcome the obstacle are increasing the professionalism quality of the teacher. It can be done by making meeting once in three months and giving professional training at local and national levels, using two language system (Java language and Indonesia language) in learning bahasaj awa,  making a meeting between teachers and parents once in six months, making rules to limit the using of handphone at school, working together with parents to supply teacher for the special need students.Key words: Education multicultural, culture and art, multicultural values.